SELEKSI VENDOR CETAK LOGO MULTI-TEKNIK: INTEGRASI ABC/XYZ DAN AHP PADA PRODUKSI MERCHANDISE - Chandra, Edy; Darmo, Budi (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2025)
Branded merchandise production often relies on multiple printing techniques—Direct Transfer Film (DTF), screen printing, and UV printing—each introducing distinct trade-offs in cost, logo reproduction quality, and delivery reliability. This study develops a structured decision framework for vendor selection in a multi-technique context. The approach comprises two stages. First, stock keeping units (SKUs) are segmented using the ABC/XYZ classification based on annual consumption value and demand variability to establish service priorities. Second, the Analytic Hierarchy Process (AHP) is applied to derive criterion weights and compute composite performance scores for candidate vendors. The evaluation matrix includes unit cost, lead time, on-time delivery rate, print defect rate, color consistency (ΔE), production capacity, and flexibility to fulfill small or urgent orders. A case analysis indicates that high-value, stable SKUs (AX) warrant vendors emphasizing quality and delivery reliability, whereas low-value, volatile SKUs (CZ) are more cost-sensitive. The framework yields primary and backup vendor recommendations for each printing technique and informs order-allocation policies consistent with demand profiles. The proposed method supports transparent, data-driven sourcing decisions for brand-logo merchandise while remaining practical for small and medium enterprises.